Ensuring transparency and traceability of food local products: A blockchain application to a Smart Tourism Region - Baralla, Gavina; Pinna, Andrea; Tonelli, Roberto; Marchesi, Michele; Ibba, Simona (Concurrency and computation, 2021)
Summary This article proposes a blockchain oriented platform to guarantee the origin and provenance of food items in a Smart Tourism Region context. Local food and beverage, in fact, can become a good combination to attract tourist and to promote the area provided that their provenance is clearly certified. We designed and developed a blockchain‐based system to manage an agri‐food supply chain for tracking food items. By using smart contracts the platform guarantees transparency, efficiency and trustworthiness. Our system is particularly suitable to manage cold chain since the system interfaces with IoT network devices providing detailed information about data monitoring food such as storage temperature, environment humidity, and GPS data. All involved actors can share data and information in a more efficient, transparent, and tamper proof way than traditional systems. The final consumer can access with transparency to all the agri‐food chain of the purchased product and verify provenance by retrieving all detailed information registered in the blockchain public ledger. The proposed system has been designed according to the ABCDE method, an agile development process recently conceived, to obtain a higher software quality to design a general blockchain system by means software engineering practices. A real case study applied to local products from Sardinia, Italy, is proposed at the end of the article.